2018
DOI: 10.1002/2017gc007089
|View full text |Cite
|
Sign up to set email alerts
|

Near Equilibrium 13C18O Bonding During Inorganic Calcite Precipitation Under Chemo‐Stat Conditions

Abstract: We report results of 13C/12C, 18O/16O, and 13C18O “clumped” isotope analyses from a series of calcite precipitation experiments from aqueous solutions under laboratory conditions. Chemo‐stat precipitation experiments were performed to synthetically form calcite from aqueous solution onto 43Ca‐labeled calcite seed crystals. Formation rate was controlled during the experiments to investigate the effect of precipitation rate and temperature on 13C18O bonding in calcite, where rates ranged from 10−6.88 to 10−8.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 89 publications
(212 reference statements)
4
17
1
Order By: Relevance
“…The Caltech clumped isotope lab consistently produces calibration lines with steeper slopes (Ghosh et al, 2006;Tripati et al, 2010;Thiagarajan et al, 2011;Eagle et al, 2013;Hines et al, 2019). Additionally, the slowest growth inorganic calcite in an inorganic calcite experiment show that  47 values are consistent with the steep slope  47 -temperature calibration of Ghosh et al 2006 (see Figure 6 and 7 in (Levitt et al, 2018)). We use two "steep-slope" calibrations (Ghosh et al, 2006;Thiagarajan et al, 2011) updated into the absolute reference frame to correct our data.…”
Section:   47 -Temperature Calibrationsupporting
confidence: 68%
See 1 more Smart Citation
“…The Caltech clumped isotope lab consistently produces calibration lines with steeper slopes (Ghosh et al, 2006;Tripati et al, 2010;Thiagarajan et al, 2011;Eagle et al, 2013;Hines et al, 2019). Additionally, the slowest growth inorganic calcite in an inorganic calcite experiment show that  47 values are consistent with the steep slope  47 -temperature calibration of Ghosh et al 2006 (see Figure 6 and 7 in (Levitt et al, 2018)). We use two "steep-slope" calibrations (Ghosh et al, 2006;Thiagarajan et al, 2011) updated into the absolute reference frame to correct our data.…”
Section:   47 -Temperature Calibrationsupporting
confidence: 68%
“…Previous work has shown that the measured oxygen isotopic fractionation of carbonates may vary depending on the rate of precipitation (McConnaughey, 1989;Watkins and Hunt, 2015;Staudigel and Swart, 2018) or may also be independent of precipitation rate (Tarutani et al, 1969;Kim and O'Neil, 1997). Similarly for clumped isotopes, an ion-by-ion growth model predicts there to be a rate dependent kinetic isotope effect on clumped isotopes (Watkins and Hunt, 2015), while observations of inorganic laboratory calcite indicate that  47 is independent of precipitation rate (Tang et al, 2014;Levitt et al, 2018). Disentangling the effects of carbonate precipitation rate on oxygen and clumped isotopes is beyond the scope of our study but is a promising line of future research.…”
Section: Ph Dic Equilibration Ph and Rate Of Precipitationmentioning
confidence: 85%
“…It is important to note that most of the data points and calibration lines are below the Daeron-Coplen equilibrium calibration. This is also the case for the data of feng et al (2014) and also valid for experiments with synthetic calcite with growth rates of several 10 -9 mmol cm -2 s -1 (Levitt et al 2018) as can be seen from fig. 6 in Johnston et al (2013).…”
Section: Caco3supporting
confidence: 88%
“…The values decrease with increasing precipitation rate. Recently Levitt et al (2018) reported of synthetical calcite precipitated close to equilibrium with rates between 10 -9 and 10 -8 mmol cm -2 s -1 . Watkins et al (2014) proposed a model that rep- Fig.…”
Section: Caco3-h2omentioning
confidence: 99%
“…those of Kim and O'Neil, 1997) kinetic effects lead to nonequilibrium calcite  18 O (e.g. Coplen, 2007;Watkins et al, 2013;Levitt et al, 2018).…”
Section: Calcite ∆47 and  O: Aquifer Fluid Temperature And O-isotopimentioning
confidence: 99%